The empowerment of women: Islamic and western perspectives - Ali, Mohd Mumtaz (Bangladesh Institute of Islamic Thought (BIIT), 2016)
In the presence of problems comforting women, several regional, national and international organizations have drawn up action plans for the empowerment of women. In spite of sincere efforts and effective strategies, problems of women continue. This paper argues that these problems are mainly caused by lack of ethical, spiritual and moral foundations in life and society. Improper education of both men and women also contributes to gender injustice. This paper contends that empowerment of women requires proper education of men and women as well as to strengthen the ethical, spiritual and moral foundations in life and society. The article further argues that Islam as the worldview, way of life, and code of conduct has the potential to provide sound ethical, spiritual and moral foundation as well as proper education to right the wrong done to women.